1999
DOI: 10.1007/s007870050133
|View full text |Cite
|
Sign up to set email alerts
|

A complex background in children and adolescents with psychiatric disorders: Developmental delay, dyslexia, heredity, slow cognitive processing and adverse social factors in a multifactorial entirety

Abstract: A consecutive cohort of 112 children, 42 girls and 70 boys, aged 5-17 years, receiving child psychiatric inpatient care, was investigated regarding the probability of a complex background of concomitant biological and social factors. Most of the subjects showed maladjustment and depressive states, school problems, problems with peers, psychosomatic complaints and anxiety. A very high rate of factors indicating neurodevelopmental dysfunctions was found particularly in boys, who exhibited developmental delay, dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…The ndings of a relation between parents' perceptions of maturational status and behaviour problems in children are supported by previous research (3)(4)(5)(6). According to Frisk, adolescents with psychiatric disorder have brain immaturity or developmental delay as a factor in their complex background (22). The importance of relating the child's development, maturational status and behaviour is put forward in the DSM-IV, for example, when evaluating ADHD symptoms (23).…”
Section: Discussionsupporting
confidence: 54%
“…The ndings of a relation between parents' perceptions of maturational status and behaviour problems in children are supported by previous research (3)(4)(5)(6). According to Frisk, adolescents with psychiatric disorder have brain immaturity or developmental delay as a factor in their complex background (22). The importance of relating the child's development, maturational status and behaviour is put forward in the DSM-IV, for example, when evaluating ADHD symptoms (23).…”
Section: Discussionsupporting
confidence: 54%
“…Anxiety-related symptoms such as lack of concentration, lack of interest and attention, distraction, emotional distress, tension, day-dreaming, phobias, fear of rejection, insecurity, aggressiveness, withdrawal and psychosomatic complaints were common findings in the case studies of children and adolescents with dyslexia who have taken part in various research efforts in the twentieth century (Frisk, 1999;Gates, 1941;Gray, 1922;Hincks, 1925;Silverman, Fite & Mosher, 1959;Swain, 1985). In a longitudinal study from pre-school to school age, Richman, Stevenson and Graham (1982) found little evidence that the children with early behavioural problems were more likely to have reading difficulties at age 8 than those without behavioural problems.…”
mentioning
confidence: 99%
“…For the experimental group, further pre-tests were also administered, speci cally the Dyslexia Screening Test and the British Picture Vocabulary Scale (Dunn et al, 1982). It is important to note the number of males and females in the experimental and comparison groups, because boys have more fragile skills in the early school years, particularly when the effects of gender are compounded by low SES (Frisk, 1999). The experimental and comparison group were matched on their ratio of male to female participants, with 64% males and 36% females in both groups.…”
Section: Selection Of Participants and Groupsmentioning
confidence: 99%